(untitled) (Fiep Bulletin - online, 2013)
With the creation of the University and the Physical Education course the weight training room of UNISC was assembled, located next to the ludic-educational gym, and received a few equipments for resistance training and exercise bikes initially aiming the teaching of subjects of the Physical Education course. The general goal of this research is to report the organizational and functional structure of the UNISC Weight Training Project, with a view toward teaching, research and extension at the University. The methodology used in this study was a documental analysis of projects and reports presented from the year 2000 to 2012. Over the years the weight training room has been structured with a variety of equipment aiming to serve also the clienteles in the morning and afternoon shifts, providing opportunities for general development in the practice of aerobic and resistance exercises. Thus, for an adequate occupation of this space the “UNISC Weight Training Project” was created as an extension project and social function, articulating teaching, research and extension. Currently the work done by the project is coordinated by three professors of Physical education with the help of three scholarship students. As for teaching the project has contributed in helping professors and/or students to develop works from subjects of the Physical Education course. The research has allowed students to participate in the selection, elaboration and presentation of abstracts and/or articles for publication as well as be in touch with researchers and works of other teaching institutions. The weight training project has contributed in the service of other institutional programs and projects, as well as to the members of the general community. As teaching action the research monograph work of a scholarship student was transformed in an article and published in an international level magazine with the title: “Aerobic and resistance training with an individual with diabetes, hypertension and obesity as a result of liver transplantation: a study in Santa Cruz do Sul, RS, Brazil”. It is believed that these data show the contribution the UNISC Weight Training Project had as social function, articulating teaching, research and extension in the institution.